2021
DOI: 10.1016/j.jbc.2021.100483
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-223-3p inhibits vascular calcification and the osteogenic switch of vascular smooth muscle cells

Abstract: Vascular calcification is the ectopic deposition of calcium hydroxyapatite minerals in arterial wall, which involves the transdifferentiation of vascular smooth muscle cells (VSMCs) toward an osteogenic phenotype. However, the underlying molecular mechanisms regulating the VSMC osteogenic switch remain incompletely understood. In this study, we examined the roles of microRNAs (miRNAs) in vascular calcification. miRNA-seq transcriptome analysis identified miR-223-3p as a candidate miRNA in calcified mouse aorta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 41 publications
1
28
0
Order By: Relevance
“…Of the 195 DEmiRNAs identified, the most was functionally annotated, such as miR-7a-5p, miR-223-3p, miR-22-3p, miR-146a-5p, miR-378a-3p, miR-467a-5p, miR-532-5p, miR-652-3p, miR-871-3p and miR-96-5p ( Coffey et al, 2019 ; Ota et al, 2019 ; Chu et al, 2020 ; Du et al, 2020 ; Liang et al, 2020 ; Yan et al, 2020 ; Wang X. et al, 2021 ; Gajeton et al, 2021 ; Han et al, 2021 ; Kinoshita et al, 2021 ). Unlike the DEmiRNAs, most of the DElncRNAs were not annotated with unknown functions.…”
Section: Resultsmentioning
confidence: 99%
“…Of the 195 DEmiRNAs identified, the most was functionally annotated, such as miR-7a-5p, miR-223-3p, miR-22-3p, miR-146a-5p, miR-378a-3p, miR-467a-5p, miR-532-5p, miR-652-3p, miR-871-3p and miR-96-5p ( Coffey et al, 2019 ; Ota et al, 2019 ; Chu et al, 2020 ; Du et al, 2020 ; Liang et al, 2020 ; Yan et al, 2020 ; Wang X. et al, 2021 ; Gajeton et al, 2021 ; Han et al, 2021 ; Kinoshita et al, 2021 ). Unlike the DEmiRNAs, most of the DElncRNAs were not annotated with unknown functions.…”
Section: Resultsmentioning
confidence: 99%
“…miR-223 regulates STAT-3 expression at the posttranscriptional level ( 9 ). In the present study, miR-223 and STAT-3 expression levels were altered to validate whether the RORĪ±-miR-223/STAT-3 signalling pathway was involved in the regulation of melatonin in ECs exposed to low shear stress.…”
Section: Resultsmentioning
confidence: 99%
“…RORĪ± regulates the expression of numerous genes at the transcriptional level and participates in a number of biological processes, including anti-inflammatory and anti-apoptotic processes ( 8 ). A previous study also revealed that microRNA (miRNA/miR)-223 inhibits signal transducer and activator of transcription 3 (STAT-3) signalling pathway activation and inhibits vascular calcification of smooth muscle cells ( 9 ). In addition, via bioinformatical analysis, the present study revealed that melatonin potentially binds to the miR-223 promoter and promotes miR-223 transcription.…”
Section: Introductionmentioning
confidence: 99%
“…Total RNAs were extracted from aortic valves and cells using TRIzol Reagent (Life technologies) as described previously (Han et al, 2021). RNA from five calcified aortic valves and 3 normal aortic valves were used for miRNA-sequencing.…”
Section: Rna Extraction and Mirna-sequencingmentioning
confidence: 99%